The ‘enabling’ master’s degree in architecture, an opportunity for experiential learning - Sauquet Llonch, Roger-Joan; Serra-Permanyer, Marta (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Schools of architecture have recently converted the former Final Degree Project into a one-year ‘enabling’ master’s degree. This is a collateral effect of adapting Spanish university studies to the European legislative framework. Faced with this challenge, the Escola Tècnica Superior d’Arquitectura del Vallès (ETSAV) proposed the implementation of a teaching model that would allow students to learn based on the experience of interaction with ‘the people’ and construction experimentation. On a methodological level, the article reviews the theoretical basis related to this model based on the condition of an open process, physical experimentation and social return. It also makes a critical approach of the three first years of the master’s degree to identify and review the teaching tools implemented, the subjects being researched and the contradictions that emerge. It concludes by evaluating the results obtained and identifying the need to balance learning between psychosocial competences and construction and technological competences, representing the main challenge and potential complexity of the service-learning projects conducted by the ETSAV’s ‘enabling’ master’s degree.